A new species of the genus Neobubastes Blackburn, 1892 from Western Australia (Coleoptera: Buprestidae: Buprestinae: Pterobothrini) - Bílý, Svatopluk; Powell, Michael (Zootaxa, 2017)
A description of Neobubastes obscura sp. nov. from Western Australia is provided. The new species is illustrated and compared with other species of the genus. A key to and images of all species of the genus Neobubastes Blackburn, 1892 are provided.